'You want to deal with power while riding on power': global perspectives on power in participatory health research and co-production approaches. Issue 11 (11th November 2021) - Egid, Beatrice R; Roura, María; Aktar, Bachera; Amegee Quach, Jessica; Chumo, Ivy; Dias, Sónia; Hegel, Guillermo; Jones, Laundette; Karuga, Robinson; Lar, Luret; López, Yaimie; Pandya, Apurvakumar; et al.
Abstract : Introduction: Power relations permeate research partnerships and compromise the ability of participatory research approaches to bring about transformational and sustainable change. This study aimed to explore how participatory health researchers engaged in co-production research perceive and experience 'power', and how it is discussed and addressed within the context of research partnerships. Methods: Five online workshops were carried out with participatory health researchers working in different global contexts. Transcripts of the workshops were analysed thematically against the 'Social Ecology of Power' framework and mapped at the micro (individual), meso (interpersonal) or macro (structural) level. Results: A total of 59 participants, with participatory experience in 24 different countries, attended the workshops. At the micro level, key findings included the rarity of explicit discussions on the meaning and impact of power, the use of reflexivity for examining assumptions and power differentials, and the perceived importance of strengthening co-researcher capacity to shift power. At the meso level, participants emphasised the need to manage co-researcher expectations, create spaces for trusted dialogue, and consider the potential risks faced by empowered community partners. Participants were divided over whether gatekeeper engagement aided the research process or acted to exclude marginalised groups from participating. At the macro level, colonial and 'traditional' research legacies were acknowledged to have generated and maintained power inequities within research partnerships. Conclusions: The 'Social Ecology of Power' framework is a useful tool for engaging with power inequities that cut across the social ecology, highlighting how they can operate at the micro, meso and macro level. This study reiterates that power is pervasive, and that while many researchers are intentional about engaging with power, actions and available tools must be used more systematically to identify and address power imbalances in participatory research partnerships, in order to contribute to improved equity and social justice outcomes.